(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2024)
Village Land Councils have been established to resolve land use conflicts in rural Tanzania. The history reveals that Tanzania has been mostly affected with the endless land based conflicts between farmers and pastoralists.The presence of VLCs in rural Tanzania has brought significant changes in rural areas where farmers and pastoralists compete to utilize and possess scarce resources. However, rural dwellers have different opinions on the worthness of the respective local organs in resolving land use conflicts between farmers and pastoralists. This study therefore intended to explore attitudes from the community members towards the capacity of the Village Land Councils in managing land use conflicts between farmers and pastoralists. Sem-structured interviews were used to collect data where semantic differential scale was used as the appropriate tool for exploring attitudes from the respondents particularly: farmers and pastoralists who mostly rely on VLCs for mediation services. NVivo software was used for analyzing such data. The results indicated that majority of respondents (farmers and pastoralists) in Mbarali and Kilosa District Councils had positive attitude towards VLCs due to their performance in resolving land use conflicts between farmers and pastoralists. Similar response was obtained from the farmers operating in Tunduru District Council. However, some pastoralists in Tunduru District Councils had remained skeptical on the capacity of the VLCs to resolve conflicts and create conducive working environment for both conflicting parties. Their doubts relied on injustice practices such as corruption, nepotism and tribalism that were directly associated with VLC members. Based on the findings, the study suggests for more capacity building programs for enhancing the capacity of VLC members to act firmly and objectively and for the community members so that they develop a sense of responsibilities in supporting the VLCs’ operations for the common good.